Karakteristik Briket Arang Sekam Padi dan Arang Kulit Bawang Putih - Mohammad Nurhilal; Roy Aries Permana Tarigan (Media Teknika, 2017)
Indonesia is endowed with abundant natural wealth capable of being transformed into an energy source. However, until now the utilization of natural resources can not be optimally processed. One alternative solution to make the fuel as a substitute for LPG is to fuel the briquettes. The general purpose of this research is the manufacture of briquettes from waste materials such as rice husk and garlic skin. While the specific purpose of this research is to know the characteristic of proximate briquettes such as: water content, ash content, fixed carbon, volatile matter, and calorie briquettes, variations of glue composition glue 200, 250, 300 gram, kanji starch composition 20, 30, and 40 gram and paper pulp 50 w / w and 100 w / w of total weight of adhesive 20 gram, and jelantah cooking oil. Methods in this research are experimental approaches such as, making briquettes, and testing the characteristics of briquettes. The results of research on water content, ash content, fixed carbon, volatile matter and calorific briquettes of rice husk huskers were 33,493%, 39,966%, 29,058%, 30,923% and 3873,500 kal / gram respectively. While the characteristics of garlic skin briquettes produced the highest price respectively 35.986%, 9.650%, 42.373%, 34.479%, and 4783.654 cal / gram.Keywords: Characteristics of briquettes, rice husk, garlic skin.